P342 Trans-continental analysis of over, 2000 Inflammatory Bowel Disease patients implicates geography, disease type, and exposure to immunosuppression as drivers of SARS-CoV-2 seroprevalence: data from the ICARUS-IBD Consortium. (21st January 2022) - Wong, S Y; Helmus, D; Marlow, L; Martinez Pazos, V; Brann, S; Wellens, J; Kedia, S; Mak, J W Y; Bergemalm, D; Argollo, M; Zaltman, C; Steinwurz, F; et al.
Abstract: Background: IBD patients on immune-modulatory therapies are considered high-risk for SARS-CoV-2 infection. Direct comparisons of serological responses to SARS-CoV-2 infection in IBD patients across different continents and medications are lacking. We performed SARS-CoV-2 sero-surveillance of IBD patients prior to vaccination at seven large tertiary centres in Asia, Europe, and North America. Methods: Clinical data and sera were collected from, 2, 213 IBD patients receiving routine care at institutions in Belgium, Canada, Hong Kong, India, Japan, the United Kingdom, and the United States between, 26 May, 2020 and, 24 September, 2021 (Table, 1). Sera were taken prior to vaccination. Clinical data were collected through patient questionnaires and medical records. Antibody reactivity to the SARS-CoV-2 spike protein was assessed using the Roche SARS-CoV-2 anti-spike total antibody and/or Siemens Healthineers COV2T anti-spike total antibody assays, which showed, 99.4% concordance. Univariate analysis was performed to evaluate association between individual variables and sero-status. Results: The pre-vaccination seroprevalence of antibodies to SARS-CoV-2 in IBD patient varied widely according to location from, 0% in Hong Kong to, 57.9% in New Delhi, India (p<0.001). Rates in Europe and North America were similar (range, 3.57%-8.94%). Overall, SARS-CoV-2 seroprevalence appears to be equal to or less than local populations (Table, 2). Seroprevalence rates were associated with IBD type (7.8% CD, 12.4% UC, 15% IBD-U, p<0.001), smoking status (p<0.001), and history of COVID diagnosis (p<0.001) or COVID hospitalization (p=0.001), and any IMM (p<0.001). (Table, 3). Whilst there were no significant differences in seroprevalence between patients receiving infliximab (IFX), vedolizumab (VDZ), and ustekinumab (UST), antibody levels were attenuated in patients on IFX monotherapy and combination therapy (both p=0.002) and VDZ (p=0.02), compared with no medications (Figure 1). Conclusion: We confirm in diverse poulations that exposure to biologics or immunomodulators, type of disease, and smoking status are associated with seroprevalence and antibody levels. We show for the first time the dominant influence of geographical location on sero-status in these patients. These observations should be considered as we look towards post-vaccination data to help stratify patients for clinical guidelines on SARS-CoV-2 vaccination.